Numerical prediction of blast fragmentation of reinforced concrete slab using ALE-FEM-SPH coupling method - Wang, Zitong; Chen, Wensu; Hao, Hong; Dong, Youkou; Huang, Zhijie (Finite elements in analysis and design, 2023)
Spalling is a typical damage mode of reinforced concrete (RC) structures subjected to blast and impact loads. Concrete debris from spalling damage could be ejected with high velocities therefore impose significant threats to surrounding structures and people. Current numerical methods such as finite element method (FEM) based on continuum damage mechanics have inherent limitations in predicting fragmentation due to element distortion caused by large deformation and heavy discontinuity, which lead to simulation overflow, while the discrete element methods and particle methods that predefine the weaker sections and particle sizes result in inaccurate fragment size and shape prediction. In this study, an Arbitrary Lagrangian Eulerian-FEM-smoothed particle hydrodynamics (ALE-FEM-SPH) coupling method is employed to predict the spalling damage of a RC slab subjected to blast load. In this method, the RC slab is modelled using Lagrangian meshes, while the air and the explosive charge are modelled using ALE meshes. In the simulation the Lagrangian elements that experienced large deformation (e.g., spalling damage) are transformed into SPH particles to avoid erosion of the elements. A modified post-process fragment recognition program is proposed to obtain the fragment characteristics (e.g., fragment size distribution and velocity). The numerical results are compared with test results by other researchers, and a good agreement is achieved in terms of the spalling area of the slab, the fragment velocity and fragment size distribution, validating the accuracy of the ALE-FEM-SPH coupling method for predicting the blast fragments of concrete structures. •ALE-FEM-SPH method to predict blast fragmentation is established.•Crack band theory can better predict fragment velocity.•3D binary graph fragment identification program is proposed for brittle material.•Fragment characteristics can be used for further risk analysis.